Implementasi Tax on Food dalam Tanggung Jawab Negara Terhadap Hak Pangan Berdasarkan Putusan Mahkamah Konstitusi 39/PUU-XIV/2016 - Intan Permata Putri; Rima Yuwana Yustikaningrum; Ananthia Ayu Devitasari (Jurnal Konstitusi, 2021)
After the Constitutional Court decision number 39/PUU-XIV/2016 concerning the Judicial Review of the Value Added Tax on Goods and Services and Sales Tax on Luxury Goods with problems related to the criteria for 11 types of food commodities not subject to Value Added Tax (VAT). However, in the a quo decision, the court expanded the meaning of 11 food commodities so that not only 11 commodities were not subject to VAT. This decision is important because it laid the foundation for guaranteeing the right to food which is the responsibility of the state. The problem is how Constitutional Court decision No. 39/PUU-XIV/2016 is implemented on the application of VAT on food commodities? How is the application of taxes on food commodities in various countries? This article is normative legal research using a conceptual approach and a comparative approach. The reference used in this article include decisions, books, journals, reports, and other references related to the issue of the right to food and the imposition of VAT on food commodities. This article concludes that first, after the Constitutional Court Decision, the Government issued the Minister of Finance Regulation No. 99/PMK.010/2020 which adds to the criteria for necessities to be 14 items. However, these criteria must constantly be evaluated and updated according to the dynamics of social, economic, nutritional, ecological, and other supporting variables; second, the tax imposed on food (tax on food) has been applied to several countries such as Denmark; Finland; Hungary; France. The amount of food that is subject to tax is of several types, such as alcohol, tobacco, foods high in sugar, salt, and saturated fat. The goal is to develop a healthy lifestyle in the community. However, none of the countries that have implemented a tax on food have included basic commodities as tax objects. The application of staples as goods subject to VAT is of course not in line with the constitution and the concept of tax on food that has existed so far.